Exploring the Mechanism of Ultrafast Intersystem Crossing in Rhenium(I) Carbonyl Bipyridine Halide Complexes: Key Vibrational Modes and Spin-Vibronic Quantum Dynamics - Harabuchi, Yu; Eng, Julien; Gindensperger, Etienne; Taketsugu, Tetsuya; Maeda, Satoshi; Daniel, Chantal (Journal of chemical theory and computation, 2016)
The mechanism of ultrafast intersystem crossing in rhenium(I) carbonyl bipyridine halide complexes Re(X)(CO)3(bpy) (X = Cl, Br, I) is studied by exploring the structural deformations when going from Franck-Condon (FC) to critical geometries in the low-lying singlet and triplet excited states and by selecting the key vibrational modes. The luminescent decay observed in [Re(Br)(CO)3(bpy)] is investigated by means of wavepacket propagations based on the multiconfiguration time-dependent Hartree (MCTDH) method. The dominant coordinates underlying the nonradiative decay process are extracted from minima, minimum energy seam of crossing (MESX) and minimum energy conical intersection (MECI) geometries obtained by the seam model function (SMF)/single-component artificial force induced reaction (SC-AFIR) approach. By choosing the normal modes used in MCTDH from the MECI and MESX geometries, not only the degenerate energy points but also the low-energy-gap regions are included. For this purpose a careful vibrational analysis is performed at each critical geometry and analyzed under the light of the pertinent nonadiabatic coupling terms obtained from the linear vibronic coupling (LVC) model augmented by spin-orbit coupling (SOC) in the electronic diabatic representation.